Whole genome and transcriptome reveal flavone accumulation in Scutellaria baicalensis roots - Hu, Suying; Wang, Donghao; Wang, Wentao; Zhang, Caijuan; Li, Yunyun; Wang, Yueyue; Zhou, Wen; Niu, Junfeng; Wang, Shiqiang; Qiang, Yi; Cao, Xiaoyan; Wang, Zhezhi (Frontiers in Plant Science, 2022)
Scutellaria baicalensis Georgi is a Lamiaceae family medicinal plant that contains high levels of 4'-deoxyflavone and other flavonoids in its roots; thus, it has strong potential as a plant resource for research into the biosynthesis of specific flavonoids. Here, we report on a chromosome-level S. baicalensis genome assembled to nine chromosomes (376.81M) using PacBio, HiSeq 10X, and Hi-C assisted assembly. The assembly ratio was 99.22 %, the contig N50 was 1.80 million and the scaffold N50 was 40.57 million, with 31896 genes being annotated. The comparative genome revealed that S. baicalensis and Salvia miltiorrhiza belonged to the same branch, with a divergence 36.3 million years ago. Other typically correlated species were Boea hygrometrica and Sesamum indicum. We investigated the structural genes involved in flavonoid synthesis in combination with transcriptome sequencing analysis for different tissues (roots, stems, flowers, leaves) of purple, pink, and white flowers. The results revealed that F6H was the key enzyme in the flavonoid synthesis pathway. S.baiMYB gene family expression pattern analysis and co-expression network analysis revealed that S.baiMYB transcription factors primarily regulated the production of flavonoids in S. baicalensis. S.baiMYB serves as a major factor in regulating flavonoid synthesis in the roots, where yeast one-hybrid assays revealed that these transcription factors might bind to the promoter regions of structural genes to control the accumulation of flavonoids. Genome and transcriptome sequencing, co-expression analysis and yeast one-hybrid experiments provided valuable genetic resources for understanding flavonoid biosynthesis in S. baicalensis. These findings provide are helpful as they provide ideas for the accumulation of metabolites in Lamiaceae.